An?lise de desempenho de redes TCP sem fio - Pinto, Bruno Couto Costa (2006)
Abstract The TCP/IP networks were designed considering the use of wired media. Although, the huge growth of the Internet together with the growth of the wireless transmissions caused the need of insertion of TCP in this new scenario. As some of the wireless networks characteristics are harmful to the standard TCP, as the higher bit error rates, the intermittent signal loss between the wireless link ends, the bandwidth asymmetry between wireless uplink and downlink and the long propagation delays in the case of the satellite links, much effort was done to adapt TCP to this new environment. The objective of this dissertation is to present some of the solutions found in the literature developed to decrease the impact of those characteristics inherent to wireless networks in the TCP performance. Besides, concerning the higher bit error rates problem, to develop an analytical model able to estimate the TCP performance when the solution to improve its performance is the use of Stop-and-Wait ARQ (Automatic Repeat Request), Go-Back-N ARQ and FEC (Forward Error Correction) error control mechanisms. In this model, adaptive systems, in what signal strength estimative is available, and non-adaptive systems are considered. With this model, we are going to analyze networks with cellular links and satellite links characteristics.